2003
DOI: 10.1074/jbc.m302517200
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-modulated Diversity of TRPV4 Channel Gating

Abstract: The TRPV4 calcium-permeable channel was cloned from mouse kidney M-1 cells, and the effect of temperature modulation on channel gating/activation by physical and chemical signals was evaluated. A TRPV4 cDNA construct with a C-terminal V5 epitope was stably transfected into human embryonic kidney (HEK) 293 and Chinese hamster ovary cells resulting in high levels of expression at the plasma membrane. Channel activation was assessed from changes in calcium influx (fura-2 fluorescence measurements) or whole cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
91
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(103 citation statements)
references
References 40 publications
7
91
0
Order By: Relevance
“…We previously demonstrated that expression of TRPV4 in keratinocytes of the rat plantar epidermis was not confined to the plasma membrane but was diffusely distributed throughout the cytoplasm, excluding the nucleus (10). Other investigators have demonstrated that a pool of recombinant TRPV4 is expressed in an apparently intracellular compartment in transfected fibroblasts (24). TRPV3 appears to exhibit a similar pattern in skin sections (3), a result we have confirmed.…”
Section: Discussionsupporting
confidence: 74%
“…We previously demonstrated that expression of TRPV4 in keratinocytes of the rat plantar epidermis was not confined to the plasma membrane but was diffusely distributed throughout the cytoplasm, excluding the nucleus (10). Other investigators have demonstrated that a pool of recombinant TRPV4 is expressed in an apparently intracellular compartment in transfected fibroblasts (24). TRPV3 appears to exhibit a similar pattern in skin sections (3), a result we have confirmed.…”
Section: Discussionsupporting
confidence: 74%
“…[Ca 2ϩ ] i Measurements-Intracellular calcium levels were measured in cells of the split-opened ASDNs using Fura-2 fluorescence ratiometric imaging as described previously (32,33). Split-opened ASDNs were loaded with Fura-2 by incubation with 2 M Fura-2/AM in a bath solution for 40 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…TRPV4 is a member of the transient receptor potential vanilloid subfamily of TRP 2 channels, and like other members of this subfamily, it is a polymodal receptor activated by a wide variety of stimuli. TRPV4 is strongly expressed in kidney and is activated by hypotonicity, which has led to the suggestion that TRPV4 is an osmosensor important in regulating body fluid levels (2,(5)(6)(7)(8)(9). However, TRPV4 is also activated by innocuous heat with a threshold of Ͼ27°C (6,10,11), by the phorbol ester 4␣-phorbol 12,13-didecanoate (12,13), by low pH (14), by endocannabinoids and arachidonic acid metabolites (15,16), by the active compound, bisandrographolide A, of Andrographis paniculata, a Chinese herbal plant (17), and by nitric oxide (18).…”
mentioning
confidence: 99%